2022
DOI: 10.3389/fonc.2022.1025060
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency is associated with gynecologic cancer recurrence

Abstract: Zinc deficiency can cause various symptoms, including hair loss, anemia, and taste disorders. Recently, the association between cancer and zinc deficiency has received much attention with respect to its antioxidant properties. However, only a few studies have investigated the association between gynecologic cancers and zinc; to date, no studies have evaluated serum zinc status at the onset of gynecologic cancer or the relationship between zinc and cancer recurrence. The objectives of the present study were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The risk of mortality is significantly higher in laryngeal cancer patients with the lowest serum zinc levels compared with the highest [183]. Zinc deficiency has been found to be an independent predictor of gynecological cancer recurrence [184]. Experimental clinical studies of small groups showed a beneficial effect of zinc supplementation on the overall survival of patients with advanced nasopharyngeal carcinoma [185].…”
Section: Zinc and Seleniummentioning
confidence: 99%
“…The risk of mortality is significantly higher in laryngeal cancer patients with the lowest serum zinc levels compared with the highest [183]. Zinc deficiency has been found to be an independent predictor of gynecological cancer recurrence [184]. Experimental clinical studies of small groups showed a beneficial effect of zinc supplementation on the overall survival of patients with advanced nasopharyngeal carcinoma [185].…”
Section: Zinc and Seleniummentioning
confidence: 99%
“…Recently, for several chronic diseases, including chronic liver disease, decreased serum zinc levels have been reported. Additionally, these patients exhibit various clinical symptoms associated with zinc deficiency ( 12 - 16 ). Zinc is widely distributed in the body, especially in the muscles (57%), bone (29%), skin (6%), and liver (5%), and is reported to be associated with skeletal muscle mass ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…To perform these functions, the concentrations of metal ions are tightly controlled, and any abnormal changes can bring detrimental consequences to human health. For example, zinc deficiency is related to growth failure and variations of Zn 2+ concentrations have been linked to diseases, such as cancer, diabetes, inflammation, and infection [4][5][6][7][8][9]. Therefore, Zn 2+ may serve as a potential biomarker for monitoring the health status of patients [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%